Analyzing the 2024 Indonesian Presidential Election’s Caricatures on the Instagram Account @KOMIKKITAIG - Nuryadi Nuryadi; Vira Destina (Fakultas Komunikasi, Sastra, dan Bahasa, 2025)
This research analyzed ten caricatures about the Indonesian 2024 presidential election posted by the Instagram account @komikkitaig from October 2023 to February 2024. This paper uses a qualitative research design to find the meanings of caricatures using Barthes' semiotic analysis which categorizes meanings into denotation, connotation and myth. The aim of this research is to describe how caricatures are used to criticize the themes around the presidential election. The results of this research show that the denotation meanings can be found in the writing and drawings of the 2024 Indonesian presidential candidates. The connotation meanings in the caricature of presidential candidates Anies-Muhaimin suggest conflict, agreement and formal while the caricatures of the presidential candidates Prabowo-Gibran suggest relaxed, sarcastic and talkative. Meanwhile, the meanings of the caricature of presidential candidates Ganjar-Mahfud suggest solidarity, harmony and professionalism. The myths in the 2024 presidential election caricatures reflect the existence of political dynasties, elections influenced by certain political powers, identity politics, money determining victory, and political solidarity.